Statins and survival outcomes in patients with metastatic renal cell carcinoma. (January 2016) - McKay, Rana R.; Lin, Xun; Albiges, Laurence; Fay, Andre P.; Kaymakcalan, Marina D.; Mickey, Suzanne S.; Ghoroghchian, Paiman P.; Bhatt, Rupal S.; Kaffenberger, Samuel D.; Simantov, Ronit; Choueiri, Toni K.; Heng, Daniel Y.C.
Abstract: Background: A growing body of evidence has demonstrated the anti-neoplastic activity of statins. The objective of this study was to investigate the effect of statin use on survival in patients with metastatic renal cell carcinoma (mRCC) treated in the modern therapy era. Patients and methods: We conducted a pooled analysis of mRCC patients treated on phase II and III clinical trials. Statistical analyses were performed using Cox regression and the Kaplan–Meier method. Results: We identified 4736 patients treated with sunitinib ( n  = 1059), sorafenib ( n  = 772), axitinib ( n  = 896), temsirolimus ( n  = 457), temsirolimus + interferon (IFN)-α ( n  = 208), bevacizumab + temsirolimus ( n  = 393), bevacizumab + IFN-α ( n  = 391) or IFN-α ( n  = 560), of whom 511 were statin users. Overall, statin users demonstrated an improved overall survival (OS) compared to non-users (25.6 versus 18.9 months, adjusted hazard ratio [aHR] 0.801, 95% confidence interval [CI] 0.659–0.972, p  = 0.025). When stratified by therapy type, a benefit in OS was demonstrated in statin users compared to non-users in individuals receiving therapy targeting vascular endothelial growth factor (28.4 versus 22.2 months, aHR 0.749, 95% CI 0.584–0.961, p  = 0.023) or mammalian target of rapamycin (18.6 versus 14.0 months, aHR 0.657, 95% CI 0.445–0.972, p  = 0.035) but not in those receiving IFN-α (15.6 versus 14.8 months, aHR 1.292, 95% CI 0.703–2.275, p  = 0.410). Adverse events were similar between users and non-users. Conclusions: We demonstrate that statin use may be associated with improved survival in patients with mRCC treated in the targeted therapy era. Statins could represent an adjunct therapy for patients with mRCC; however, this is hypothesis generating and requires prospective evaluation. Highlights: Growing evidence demonstrates that statins have anti-cancer properties. Statin use improved survival in patients with metastatic renal cell carcinoma. The benefit of statins was seen in patients receiving targeted therapy in the modern era.